Youth justification of informality in the post-Yugoslav countries: Reflection of political socialization or pragmatism? - Gvozdanović Anja (Anali Pravnog Fakulteta u Beogradu)
Informal practices are rather widespread in post-Yugoslav societies, representing a complex problem with significant social, economic and political implications. The study investigates the factors that determine or contribute to shaping young people's benevolent attitude towards certain types of informality, by exploring the determinants of informality justification or permissiveness towards certain forms of informal practices. Firstly, justification of informal practices are observed as a reflection of youth political socialization, which imply their relation to the political system and democratic values. Secondly, this type of justification potentially stems from their rational evaluation of institutional performance by estimating the necessity of informality as a mechanism to navigate the perceived inefficiencies of formal institutions. By examining these dimensions, the aim is to detect the extent to which these two sets of factors contribute to young people's justification of informality in the post-Yugoslav context.